Bisphenol A exposure is involved in the development of Parkinson like disease in Drosophila melanogaster. (March 2020) - Musachio, Elize Aparecida Santos; Araujo, Stífani Machado; Bortolotto, Vandreza Cardoso; de Freitas Couto, Shanda; Dahleh, Mustafa Munir Mustafa; Poetini, Marcia Rósula; Jardim, Eliana Fernandes; Meichtry, Luana Barreto; Ramborger, Bruna Piaia; Roehrs, Rafael; Petri Guerra, Gustavo; Prigol, Marina
Abstract: The pathogenesis of Parkinson's disease has not been fully clarified yet but its cause is known to be multifactorial. One of these factors is oxidative stress induced by exposure to environmental toxifiers. We studied the effect of Bisphenol A (BPA) at concentrations of 0.5 mM and 1 mM, the concentration of 1 mM corresponding to Lowest Observed Adverse Effect Level (LOAEL) for humans in adult Drosophila melanogaster . The BPA induced oxidative stress was established by increased levels of malondialdehyde, reactive species, and decreased activity of the antioxidant enzymes superoxide dismutase and catalase, and detoxificant enzyme glutathione-S-transferase. Associated with oxidative stress, there was a reduction of acetylcholinesterase activity and a reduction of dopamine levels, which are related to the decreased locomotion activity as observed in negative geotaxis, open field and equilibrium behaviors in group exposed to 1 mM of BPA. Oxidative stress also impaired mitochondrial and cellular metabolic activity in the head causing an increase in the mortality of flies exposed to both BPA concentrations. Therefore, BPA induced Parkinsonian-like changes in flies and it is possible that the oxidative stress is closely related to this effect, providing new insights for future studies. Graphical abstract: Image 1 Highlights: Bisphenol A causes neurotoxicity in adult Drosophila melanogaster. Bisphenol A decreases locomotor capacity in Drosophila melanogaster. Bisphenol A induced Parkinson's like disease in Drosophila melanogaster.